Evaluation of flow and filling of root canal sealers using different methodologies - Fernanda Ferrari Esteves TORRES; Juliane Maria GUERREIRO-TANOMARU; Jader Camilo PINTO; Idomeo BONETTI-FILHO; Mário TANOMARU-FILHO (Universidade Estadual Paulista, 2020)
Abstract Introduction Flow and filling ability of root canal sealers are indispensable for hermetic sealing of the root canal. Micro-computed tomography (micro-CT) can be used as a complementary methodology to evaluate such properties. Objective To evaluate the flow and filling ability of AH Plus, Endofill and Sealapex by conventional methodology and micro-CT. Material and method The flow of the sealers was analyzed according to ISO 6876/2012 and complemented by the area evaluation. Glass plates were manufactured with diameters of 1×1×2 mm and 1×1×1 mm (length, width and height), with a central cavity and four grooves in the horizontal and vertical directions. Each material was placed in the central cavity. Another glass plate and a metal weight were placed on the cement and kept for 10 minutes. The glass plate/sealer set was scanned using micro-CT. The flow was calculated by linear measurement of the material in the grooves. The central filling (mm3) was calculated in the central cavity and the lateral filling was measured up to 2 mm from the central cavity. Data were submitted to ANOVA/Tukey tests (α=0.05). Result All evaluated sealers presented flow according to ISO 6876 standards. The materials showed central cavity filling capacity higher than 80% and lateral filling greater than 75%. There was no difference in flow (mm and mm2) and in the filling ability (mm3) provided by the materials (p>0.05). Conclusion All evaluated root canal sealers showed adequate flow and filling capacity, suggesting their clinical application.